Una perspectiva modular de la adaptación biológica - Dressino, Vicente (2010)
Adaptation is a central and widely discussed concept in modern evolutionary biology; however, it is necessary to rethink its significance given the complexity of the adaptive phenomenon, the development of biology and the emergence of new disciplinary fields in recent years. In this sense, we address the need to develop new conceptual perspectives that may provide a better understanding of this phenomenon. This paper aims to analyze the advantages of a modular approach in developing a more comprehensive notion of adaptation. A modular concept of adaptation would solve diverse kinds of problems, for example, the integration between the different levels of biological organization that are involved necessarily in every adaptive process.